The soul of theological anthropology: a Cartesian exploration - Farris, Joshua R. (Routledge new critical thinking in religion, theology and biblical studies, 2017)
A Cartesian exploration in tradition -- Cartesian souls and theological Prolegomena -- A Cartesian exploration in natural theology and Prolegomena -- A Cartesian exploration in the story of scripture and personal ontology -- Creation and the origin of souls -- A Cartesian exploration of the soul's origin, part 1 -- A Cartesian exploration of the soul's origin, part 2 -- A Cartesian exploration of the embodied soul -- Hamartiology, soteriology and Cartesian souls -- A Cartesian exploration of the soul's origin, original sin, and Christology -- A Cartesian exploration of the interim state and the Visio Dei -- Cartesian souls and personal eschatology -- Picturing the interim state as a Cartesian -- A Cartesian exploration of personal